1976
DOI: 10.1111/j.1699-0463.1976.tb01933.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPID DIAGNOSIS OF ENTEROBACTERIACEAE

Abstract: The paper describes a number of tests for the rapid detection of glycosidases including α‐glucosidase, β‐glucosidase, β‐glucuronidase, β‐xylosidase and α‐fucosidase. The methods use heavy suspensions of viable but non‐multiplying bacteria in a buffered solution of a chromogenic substrate. The results of the tests are readable within 4 h. The application of these tests to a collection of 633 strains of Enterobacteriaceae and Vibrionaceae demonstrates that some of the tests may be valuable additions to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…No GUD activities were observed for the non-target bacteria and this finding is in the agreement with the previous research that "species of Klebsiella do not normally express GLUase activity" (Brenner et al 1993). Furthermore, studies have been performed on the GUD activities of the Enterobacteriaceae and E. coli and confirmed that GUD activity was mostly limited to (Kilian and Bülo 1976). In the Enterobacteriaceae genus, only 20% to 29% of the Salmonella isolates tested showed GUD positive activities (Kilian and Bülo 1976;Massenti et al 1980;Feng and Hartman 1982;Frampton and Restaino 1993).…”
Section: Specificity Of Mug Assays For the Detection Of Non-target Bamentioning
confidence: 93%
See 4 more Smart Citations
“…No GUD activities were observed for the non-target bacteria and this finding is in the agreement with the previous research that "species of Klebsiella do not normally express GLUase activity" (Brenner et al 1993). Furthermore, studies have been performed on the GUD activities of the Enterobacteriaceae and E. coli and confirmed that GUD activity was mostly limited to (Kilian and Bülo 1976). In the Enterobacteriaceae genus, only 20% to 29% of the Salmonella isolates tested showed GUD positive activities (Kilian and Bülo 1976;Massenti et al 1980;Feng and Hartman 1982;Frampton and Restaino 1993).…”
Section: Specificity Of Mug Assays For the Detection Of Non-target Bamentioning
confidence: 93%
“…The enzymatic detection of the indicator of fecal contamination E. coli via its marker enzymes GUD and the marker for coliforms, GAL, have been widely used (Kilian and Bülo 1976;Edberg and Kontnick 1986;Berg and Fiksdal 1988;Rice et al 1990;Hattenberger et al 2001). Considering that E. coli is employed as an indicative microorganism of wastewater and sewage contamination, the GUD-based assays and rapid tests are important in environmental monitoring where test simplicity and speed coupled with high sensitivity are critical features.…”
Section: Bacterial Cell Enzymes As Biosensing Materialsmentioning
confidence: 99%
See 3 more Smart Citations